The internet of things from data to insight - Davies, J (N. John); Fortuna, Carolina 1982- (Hoboken, NJ John Wiley & Sons, Inc, 2020)
"The Internet of Things has been a recurrent theme among commentators since the term was coined in the late 1990s. This term has evolved from Radio Frequency Identifier (RFID) which represented a hardware related break-through that aimed to connect everyday objects in a network. IoT went beyond the initial hardware world innovation, and focused more on developing new types of sensors and sensing materials as well as on developing new communication technologies and protocols. As a result, a wide variety of communication technologies emerged in the 2000s able to support ubiquitous deployment of a wide variety of sensors. In the last decade, the focus of IoT has shifted to the data collection and processing level. Provides a comprehensive overview of the full Internet of Things technology stack with focus on data driven aspects from data modelling, processing to presentation for decision making. Explains how IoT technology is applied in practice and the benefits being delivered. Acquaints readers that are new to the area with concepts, components, technologies and verticals related to and enabled by IoT. Gives IoT specialists a deeper insight to data and decision-making aspects as well and novel application areas"--
Includes bibliographical references and index
Keywords: Internet of things